Fruit characteristics and ripening indicators of Kara Mandarin (Citrus reticulata) in Kabacan, Cotabato, Philippines - Gutierrez, Herminigildo M. (2009)
This study examined the relationship among physical, chemical and other characteristics of mature fruits from 6-year-old USM-grown Kara Mandarin (Citrus reticulata) trees. The results showed that juice volume could be estimated adequately from physical properties such as fruit diameter, weight and circumference. Sweetness of the juice was found to be significantly correlated with juice pH, acidity and TSS/A ratio. These three variables could be used to determine the readiness of the fruits for harvesting; to obtain sweet or very sweet fruits, the values of pH and TSS/A ratio should be more than 3 and 14, respectively. Fruit color and electrical resistance were found to have no significant correlation with sweetness and could not be used as ripening indicators. Juice volume could be estimated using physical measurements such as diameter, circumference and fruit weight. The % juice volume (as percentage of fruit volume), on the other hand, was significantly correlated with fruit density (positively) and rind thickness (negatively), and averaged 41.4%. This implied more juice per unit weight with denser fruits and thinner rinds.
Keywords: Citrus fruits; Kara Mandarin--Citrus varieties; Mindanao studies